Exploration of Performance Kinetics and Mechanism of Action of a Potential Novel Bioflocculant BF-VB2 on Clay and Dye Wastewater Flocculation - Bisht, Varsha; Lal, Banwari (Frontiers in Microbiology, 2019)
This study explores production of an efficient bioflocculant; BF-VB2, by strain Bacillus sp. TERI VB2 and proposes its potential application in wastewater treatment. 1 mg of BF-VB2 can effectively flocculate 1980.0 mg±5.0 mg of kaolin particles leading to 99.0%±0.5% enhancement in flocculation activity and 99.6%±1.0% reduction in turbidity; in less time. BF-VB2 when applied for treatment of textile dyeing industrial wastewater revealed reduction in dye color (82.78%±3.03%), COD (92.54%±0.24%), TSS (73.59%±0.71%), and chloride ions (81.90%±0.716%). The best-fit kinetic model, (for both COD removal, and dye decolorization) was pseudo-first order with regression coefficient of 0.98 and 0.95, & rate constant of 4.33x10-2 and 1.83x10-2, respectively. Bridging due to presence of surface charges have been proposed as flocculation mechanism. From results obtained during test-tube studies, flocculation in larger volumes (0.01 L to 5.0 L) was also performed to intend taking up BF-VB2 for in situ industrial wastewater treatment. This eco-friendly polysaccharide bioflocculant had longer shelf-life, stability to pH and temperature, cation-independence, and emerged to be more efficient than other flocculants assessed. This study proposed BF-VB2 as a potential natural flocculant candidate for industrial application.